2020
DOI: 10.3390/s20051386
|View full text |Cite
|
Sign up to set email alerts
|

Large-Area Resistive Strain Sensing Sheet for Structural Health Monitoring

Abstract: Damage significantly influences response of a strain sensor only if it occurs in the proximity of the sensor. Thus, two-dimensional (2D) sensing sheets covering large areas offer reliable early-stage damage detection for structural health monitoring (SHM) applications. This paper presents a scalable sensing sheet design consisting of a dense array of thin-film resistive strain sensors. The sensing sheet is fabricated using flexible printed circuit board (Flex-PCB) manufacturing process which enables low-cost a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Even if several authors investigated sensing ability of PP/CNT alone [36][37][38][39][40][41][42], to the best of our knowledge, no studies investigated the possibility to use PP/CNT strain sensors directly embedded in cementitious materials. Several authors proposed the use of sensing skins or sensing elements to be applied on external surfaces of buildings/infrastructures [53][54][55][56][57]. Nevertheless, the application of sensing skins requires specialized technicians and constant maintenance due to durability issues, increasing the cost and delaying the entry into service of the building or the infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Even if several authors investigated sensing ability of PP/CNT alone [36][37][38][39][40][41][42], to the best of our knowledge, no studies investigated the possibility to use PP/CNT strain sensors directly embedded in cementitious materials. Several authors proposed the use of sensing skins or sensing elements to be applied on external surfaces of buildings/infrastructures [53][54][55][56][57]. Nevertheless, the application of sensing skins requires specialized technicians and constant maintenance due to durability issues, increasing the cost and delaying the entry into service of the building or the infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the implementation of the full-Wheatstone-bridge circuit, demonstrated in Figure 4a is very effective in compensating for temperature sensitivity. In terms of the electrical configuration, the sensor demonstrated in this study ( Figure 4b) does not differ from the conventional full-bridge sensors that are commercially available or developed by other researchers [14,17]. It is composed of four resistive sensing elements (R1, R2, R3 and R4).…”
Section: Full Wheatstone Bridge Strain Sensormentioning
confidence: 98%
“…Another study showed a sensing sheet incorporating full Wheatstone bridge strain sensors fabricated on a flexible substrate using a photolithography etching process. The sensing sheet was analyzed during a several-hours-long field test on a concrete bridge to measure static strains [17]. Other very promising studies on the development large-area sensing systems includes capacitive sensors [18,19], and sensor arrays incorporating Lead Zirconate Titanate (PZT) piezoelectric sensors [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, an array of commercial metal foil strain gauges bonded to a flexible substrate detected and quantified cracks in structural materials [ 13 ]. Further studies presented another type of sensing sheet that incorporated constantan-based (Cu-Ni alloy) strain sensors that were fabricated on a flexible substrate using a photolithography etching process [ 14 ]. The signal stability of the sensing sheet was analyzed in a laboratory test, and the results revealed a 3 drift over two days of analysis.…”
Section: Introductionmentioning
confidence: 99%